POMEGRANATE SEED OIL (PUNICA GRANATUM L.), STUDY OF PHYSICAL AND CHEMICAL PROPERTIES (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Pomegranate seed oil, also known as Punica granatum seed oil, is a valuable natural resource obtained from the seeds of the pomegranate tree (Punica granatum). Pomegranate is a fruit known for its antioxidant and health benefits contained in its seeds. Pomegranate seed oil has long attracted the attention of researchers and manufacturers of cosmetic and medical products due to its amazing characteristics and potentially beneficial properties.The main importance of pomegranate oil lies in its unique composition, including its high content of fatty acids, antioxidants, vitamins and biologically active substances. Its rich composition gives it many beneficial properties, including antioxidant and anti-inflammatory properties, the ability to improve skin conditions, and potential medical uses.In this review, we will look at the composition and properties of pomegranate seed oil, as well as research related to its effectiveness in cosmetic and medical applications. We also discuss the potential limitations and challenges facing the use of pomegranate oil and its role in the beauty and health market. This review aims to highlight the importance of pomegranate oil as a natural resource that can enrich our lives and improve our skin and health.